2016
DOI: 10.1177/0886260515584349
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Pregnant Young Women

Abstract: This article explores intimate partner violence (IPV) as experienced by young women during the perinatal period. Using purposive sampling, data pertaining to the experiences of 10 young mothers were gathered through on-site participative observation and individual in-depth interviews. Interviews were coded in an inductive way to reflect the experiences of the participants before pregnancy and following pregnancy confirmation. Overall, the analyses of different manifestations of IPV and their contexts reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Levesque and Chamberland found that overall, young mothers find it difficult to identify themselves as victims of IPV and label their partner’s actions as violent. 48 Identification of IPV when risk factors, even when victims and perpetrators are in denial, is important in treating co-morbidity as in the example of drug abuse treatment and IPV. With separation and divorce being a triggering event for violence in a relationship, court professionals bear responsibility in identifying when there are IPPs and IPVs and change course accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Levesque and Chamberland found that overall, young mothers find it difficult to identify themselves as victims of IPV and label their partner’s actions as violent. 48 Identification of IPV when risk factors, even when victims and perpetrators are in denial, is important in treating co-morbidity as in the example of drug abuse treatment and IPV. With separation and divorce being a triggering event for violence in a relationship, court professionals bear responsibility in identifying when there are IPPs and IPVs and change course accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, mothers experiencing prenatal violence report worrying that IPV is harming the growth and health of their baby in utero, including concerns that the baby is aware of and experiencing problematic effects from the violence (Alhusen & Wilson, 2015). Research also indicates that pregnant women recognize the negative effect that IPV can have on children and try to modify their behavior to protect their baby (Alhusen & Wilson, 2015; Lévesque & Chamberland, 2016). Such findings show that pregnant women recognize the gravity of IPV exposure on their unborn children and try to prioritize the safety of the baby, yet these proactive behaviors are interwoven with worry about their ability to protect the baby and fears for the baby’s development.…”
Section: Ipv and Parentingmentioning
confidence: 99%
“…A recent systematic review of 92 studies indicated that women abused prepregnancy have four times higher odds of being a victim of IPV during pregnancy than peers without IPV history (James et al, 2013). The reasons for this phenomenon remain uncertain; however, it is likely that the women are stressed by parenthood responsibilities (Alio et al, 2013) and the unborn child's wellbeing when living with an abusive partner (Sylvie & Claire, 2015). They also experience mixed emotions between leaving the aggressive partners to protect the child (Engnes et al, 2012).…”
Section: Childhood Trauma and Pre-existing Ipvmentioning
confidence: 99%
“…Although many studies found a binary association between young maternal age and high prevalence of p-IPV, some studies found that this association became nonsignificant after controlling in the multivariate analysis (Finnbogadottir et al, 2016b;Globevnik Velikonja et al, 2018;Iliyasu et al, 2013). This may occur because young women (<25 years old) are more likely to be sexually abused (Miller et al, 2014;Sylvie & Claire, 2015) and be reproductively controlled by partners, which correlates with unwanted pregnancy (Miller et al, 2010). Therefore, young age could be considered a confounder of p-IPV in some societies, and this requires careful control in future investigation.…”
Section: Pregnancy-related Factorsmentioning
confidence: 99%